Analysis of Intimate Femicide Acts against Women in Gender Power Relations: Case Study in West Bandung Regency - Muhammad Riyadi Setiyawan; Zahra Fitriana Ramadhani (Journal of Feminism and Gender Studies, 2025)
This study aims to explore femicide as the most extreme form of gender-based violence, focusing on the 2022 case of Wiwin Sunengsih in West Bandung Regency. The research emphasizes the need to understand femicide not merely as an individual criminal act, but as a systemic manifestation of patriarchal power that perpetuates fear, control, and the silencing of women. Using an empirical legal approach, this qualitative research employs a descriptive method to examine how law functions in society, particularly in the enforcement and institutional responses to femicide. A case approach is used to analyze the application of legal norms in practice, supported by in-depth interviews and participatory observation. Data were collected from purposively selected informants, including law enforcement officers and officials from a women's protection agency. The findings reveal that the femicide of Wiwin was the culmination of prolonged gender-based violence and power imbalances within an intimate relationship. The legal apparatus failed to provide preventive protection despite repeated threats reported by the victim's family. From a radical feminist perspective, this case reflects how women’s bodies and lives become battlegrounds for male control, legitimized by social norms. The study also demonstrates that the legal system's formal neutrality often disregards the vulnerability of women, highlighting the need for structural legal reform. Thus, femicide must be addressed through gender-sensitive and preventive legal frameworks that go beyond punitive responses.